2018
DOI: 10.22207/jpam.12.4.24
|View full text |Cite
|
Sign up to set email alerts
|

Characterization, Phylogenetic Analysis and Potential Applications of Heterotrophic Bacteria Inhabit Sand Dunes of Thar Desert, India

Abstract: Microorganisms inhabit extreme environments are novel in terms of phylogeny and also valuable source of extracellular hydrolytic enzymes. The present study focused on isolation and characterization of moderately thermophilic heterotrophic bacteria from Thar Desert using culture dependent method and assessment of their potential for production of industrially important enzymes. Screening of bacteria from sand dune samples collected from arid region of India led to isolation of total eight moderately thermophili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 49 publications
(55 reference statements)
0
1
0
Order By: Relevance
“…Obeidat (2017) reports that B. paralicheniformis isolated from Dead Sea black mud was classified as an extremely halotolerant and exhibited esterase activity on API ZYM tested. Another study concluded that Bacillus paralicheniformis isolated from the dunes of the Thar Desert in India as a moderately thermophilic strain and showed an ability to produce extracellular lipase (Neelam et al, 2018).…”
Section: Dna-fingerprint Of Lpmhb In Genus Bacillusmentioning
confidence: 99%
“…Obeidat (2017) reports that B. paralicheniformis isolated from Dead Sea black mud was classified as an extremely halotolerant and exhibited esterase activity on API ZYM tested. Another study concluded that Bacillus paralicheniformis isolated from the dunes of the Thar Desert in India as a moderately thermophilic strain and showed an ability to produce extracellular lipase (Neelam et al, 2018).…”
Section: Dna-fingerprint Of Lpmhb In Genus Bacillusmentioning
confidence: 99%